Ademia: Agamben and the Idea of the People - Fusco, Gian Giacomo (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
In the volume Stasis. Civil War as a Political Paradigm, the Italian philosopher Giorgio Agamben advances the thesis that ademia – the absence of a people (a-demos) – is a constitutive element of the modern state. When confronted with the fact that modern political and juridical thought elevated the people to the role of the sole chief constituent agent and the ultimate source of the legitimacy of constituted orders, this thesis turns out to be rather problematic. In this work, I will explore Agamben’s notion of ademia, retracing the main lines of its theoretical development and reconsidering it in relation to different interpretations of the idea of the people. Most notably, I will demonstrate how Jean-Jacques Rousseau and Carl Schmitt in challenging the conundrums that the idea of the people inevitably entails ended up in revealing the ultimate absence of the people in the political space of the constituted order of the state. In doing so, I will try to show how Agamben’s notion of ademia is helpful is grasping some of the main paradoxes and conundrums underpinning the meaning and the uses of the idea of the people in legal and political thought.